Wind and Anchor, Roots and Wings - Wyatt, Peter (Toronto journal of theology, 2008)
Yesterday afternoon, this year's gold medallist in the Emmanuel M. Div. program was ordained in Hillcrest Christian Church (Disciples of Christ). When it came time for the act of ordination, various elders and ministers were invited to join in laying on hands with prayer for our sister Jennifer. But so were all members of the congregation who cared to. So imagine about a dozen of us robed, with hands on Jennifer's head or shoulders and others with their hands on our shoulders, and still others with hands touching their shoulders. Then came the prayer to the Holy Spirit that Jen would be filled with gifts and graces to minister faithfully in Christ's name. .